2020
DOI: 10.1016/j.lwt.2019.108693
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and chemical composition of camel and cow milk powders’ surface

Abstract: This study aimed at investigating the chemical composition and microstructure of spray dried camel and cow milk powders' surfaces with two different milk-fat contents (1 and 20g 100 g −1). The SEM (Scanning Electron Microscopy) micrographs showed that spherical particles with a 'brain'-type surface for both milk powders were produced. The surface roughness (Ra) of whole (WDMP) and skimmed (SDMP) camel milk powders (Ra = 7.6 ± 0.4 nm and 5.6 ± 0.7 nm, respectively) were significantly lower as compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Similar observations were reported by Zouari, Schuck et al. (2020). The latter indicated that camel milk fat was homogeneously distributed in the camel milk powder showing higher encapsulation degree.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Similar observations were reported by Zouari, Schuck et al. (2020). The latter indicated that camel milk fat was homogeneously distributed in the camel milk powder showing higher encapsulation degree.…”
Section: Resultssupporting
confidence: 92%
“…This observation indicated that the fat did not interact with water during water activity measurement. Actually, it was demonstrated that fats were considered as nonreacting component with water and had no influence on the water activity of milk powders (Jouppila, Kansikas, & Roos, 1997; Zouari, Schuck et al., 2020). In addition, Schuck et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations